Nutritional value of raw and extruded chickpeas (Cicer arietinum L.) for growing chikens - Brenes, A.=700 1 Viveros, A.; Centeno, C.; Arija, I.; Marzo, F.
(En, Es)
Ilus., 46 ref.
Keywords: AVES DE CORRAL; POLLO; VALOR NUTRITIVO; CICER ARIETINUM; EXTRUSION; LEGUMINOSAS DE GRANO; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH